Wind Tunnel Test of the Icing Characteristics of Airfoil Rotating around a Vertical Axis - Yan Li; Lei Shi; Wenfeng Guo; Ce Sun; Yu Jiang (International Journal of Rotating Machinery)
To determine the process of icing on the rotating machinery, an icing experiment on a rotating airfoil blade was carried out in this paper. First, an icing wind tunnel was fabricated, and its conditional parameters were calibrated. The calibration results showed that the performance of this icing wind tunnel was reliable and stable. The experimental temperature was -15°C, and the MVD was 50 μm. Then, an icing experiment on the rotating blade with the NACA0018 airfoil was carried out. The characteristics of icing, including icing distribution, growth rate of icing, and thickness of the ice layer, were defined and quantitatively analyzed under different tip speed ratios and setting angles. The results show that the type of icing changes from rime ice to glaze ice with an increase in the tip speed ratio. The dimensionless icing area and dimensionless thickness of the ice layer both increase with an increase in the icing time. The growth rate of icing increases rapidly at the initial icing stage and then decreases dramatically under each tip speed ratio condition.